1998
DOI: 10.1089/hyb.1998.17.73
|View full text |Cite
|
Sign up to set email alerts
|

Random Expression of Human Immunodeficiency Virus-1 (HIV-1) pl7 (Epitopes) on the Surface of the HIV-1-Infected Cell

Abstract: Twenty monoclonal antibodies (MAbs) were obtained by immunizing Balb/c mice with recombinant p17 (rp17) of HIV-1. Epitope specificity of each MAb was determined using six peptides that cover the entire region of p17. We found that each MAb reacts with only one of the peptides, residues 12-29, 30-52, 53-87, and 87-115 (P12-29, P30-52, P53-87, P87-115) of p17 with the exception of one MAb. Three kinds of MAbs that recognize P30-52, P87-115, and a conformational epitope, suppressed the infectivity of HIV-1 (JMH-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…Immunofluorescence staining of HIV-1-infected cell lines showed that different antigenic regions of p17 were found to be randomly expressed on the outer leaflet of live cell plasma membrane during HIV-1 replication4950. In particular, at least three regions of p17 (aa.12–29, 53–87, 87–115) were constantly detected on the cell surface by different anti-p17 mAbs, used as specific reagents, whereas other epitopes, even conformational, were occasionally expressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunofluorescence staining of HIV-1-infected cell lines showed that different antigenic regions of p17 were found to be randomly expressed on the outer leaflet of live cell plasma membrane during HIV-1 replication4950. In particular, at least three regions of p17 (aa.12–29, 53–87, 87–115) were constantly detected on the cell surface by different anti-p17 mAbs, used as specific reagents, whereas other epitopes, even conformational, were occasionally expressed.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, at least three regions of p17 (aa.12–29, 53–87, 87–115) were constantly detected on the cell surface by different anti-p17 mAbs, used as specific reagents, whereas other epitopes, even conformational, were occasionally expressed. Based on the evidence that these mAbs lacked HIV-1 neutralizing activity, the authors concluded that the reactive epitopes of p17 were not the portions of viral protein in the virion itself, but more likely short polypeptide chains of p17 transported to the surface of HIV-1-infected cells50. More interestingly, p17 secretion has been hypothesized also in patients undergoing successful cART, since the viral protein was easily detected at nM concentration in the blood of cART-treated HIV-1-seropositive patients16.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins were resolved by SDS–polyacrylamide gels (4–12%) and transferred to nitrocellulose membranes by using iBlot (Invitrogen). The membranes were treated with mouse anti-MA monoclonal antibody (29), mouse anti-CA monoclonal antibody (Advanced Biotechnologies Inc., Columbia, MD, USA), rabbit anti-NC polyclonal antibody, and rabbit anti-p6 polyclonal antibody (30). ECL Western blotting detection reagents (Nacalai Tesque, Kyoto, Japan) were used for signal detection with horseradish peroxidase conjugated anti-mouse and anti-rabbit IgG (Vector Laboratories, Burlingame, CA, USA).…”
Section: Methodsmentioning
confidence: 99%
“…39,40 The viral protein sequence contains T cell epitopes, which are relatively conserved across different HIV-1 clades. 41 Further, the discovery of p17 epitopes on the surface of HIV-1 infected cells 42 suggests that p17 epitopes are potentially promising antigenic candidates for inclusion in a vaccine strategy. The objective of the present study was also to identify an efficient AT20-KLH plus p17 vaccination…”
Section: Discussionmentioning
confidence: 99%